The rightly-guided caliphs: the range of views preserved in Hadith - Melchert, C (Bloomsbury Publishing, 2019)
Sunni hadith literature of the ninth century preserves numerous different opinions as to which caliphs were righteously guiding and guided. There is support for a theory of just two, Abu Bakr and 'Umar, for these two plus 'Uthman, for these three plus 'Ali, with variants that give only half-honours to 'Uthman or 'Ali. It is hard only to find hadith in these collections preferring 'Ali to 'Uthman, although some prominent Sunni traditionists were quoted as upholding such a preference. The suggestion seems to be that some disagreement was legitimate and should not occasion fighting.